2021
DOI: 10.7575/aiac.alls.v.12n.3.p.127
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Humor Integration in Tunisian Tertiary English Classes: A Comparative Study of Teachers’ and Learners’ Perceptions

Abstract: This study examines lecturers’ and learners’ perceptions on humor use in Tunisian tertiary classrooms, focusing specifically on the English major. The ultimate aim is to explore the types and frequency of humor use on the one hand and whether teachers regard humor in the same light as their students on the other. To this purpose, a mixed-methods approach consisting of questionnaires and semi-structured interviews is adopted to collect quantitative and qualitative data for analysis. The findings revealed that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…While previous works had different methods to measure humor rates and locate humorous messages [ 13 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], in our study, we decided to locate the humor instances using the special markup "Laughter" found in the TED Talks transcripts. This markup occurs whenever the audience laughs during the presentations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While previous works had different methods to measure humor rates and locate humorous messages [ 13 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], in our study, we decided to locate the humor instances using the special markup "Laughter" found in the TED Talks transcripts. This markup occurs whenever the audience laughs during the presentations.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, more recent research on instructional humor frequency focuses on self-reported measures. Moreover, frequency counts were obtained via survey forms or ratings rather than through actual counts of humor instances [ 45 , 46 , 47 , 48 ]. However, using self-reported measures yields lower rates of instructional humor [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation